Cultivating Local Wisdom in Character Education: Lessons from Family Education Values of Indonesian Traditional Ceremony - Testiani Makmur; Wenny Dastina (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2018)
The tradition of establishing a house in Tanjung Pauh, Kerinci contains noble educational values such as deliberation, mutual cooperation, togetherness, knowing and helping each other, monotheism, recalling kindness, and courtesy. Those values are aligned with the concept of character education proposed by Thomas Lickona. The values can be implemented into family education especially in rural communities of Tanjung Pauh, Kerinci. The character values in harvesting rice carried out by the community teach civilized attitude towards plants and sharing with others. Besides, the community also has principles of respect, attention, respect, and compliance with customs regulations. The ceremony is performed based on custom and religious teachings with the intention to reject any disasters experienced by human beings, plants, and animals. Besides, the ceremony performed contains meanings of gratitude to God Almighty in order to reduce the punishment of the grave space, especially for parents who died and owned rice fields. For those who are still alive, these activities are carried out with the hope that everything done runs well, gains healthy bodies and longevity.